Students' Mathematical Reflective Thinking Ability Through the Process of Making Telong-Telong Using the Problem-Based Learning Approach - Fina Oktavia; Kashardi Kashardi; Risnanosanti Risnanosanti (MASI Mandiri Edukasi, 2025)
This research aims to identify and analyze students' mathematical reflective thinking abilities through a Problem-Based Learning (PBL) approach, focusing specifically on making